2019
DOI: 10.1002/jcb.29577
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes related to low‐grade glioma progression and prognosis based on integrated transcriptome analysis

Abstract: Glioma is one of the most common types of human brain tumor, with high mortality in high-grade gliomas (HGG). Low-grade gliomas (LGG) can progress into HGG, leading to poor prognosis. However, it is unclear what factors affect the progression of LGG to HGG. This study aims to explore the function of the crosstalk genes on the progression and prognosis of LGG using bioinformatics analysis. Integrated transcriptome analysis was used to screen differentially expressed genes (DEGs). Then, gene ontology (GO) functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…It has been reported that collagen type V is highly expressed in the matrix of pancreatic ductal adenocarcinoma and may affect the malignant phenotype of various pancreatic cancer cell lines by promoting adhesion, migration, and viability (20). Many studies have demonstrated that COL5A2 is differentially expressed in various tumors and is related to tumor metastasis and poor prognosis (21)(22)(23). However, up to now, the role of COL5A2 in PCa has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that collagen type V is highly expressed in the matrix of pancreatic ductal adenocarcinoma and may affect the malignant phenotype of various pancreatic cancer cell lines by promoting adhesion, migration, and viability (20). Many studies have demonstrated that COL5A2 is differentially expressed in various tumors and is related to tumor metastasis and poor prognosis (21)(22)(23). However, up to now, the role of COL5A2 in PCa has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study has been found collagen genes were related to the progression and prognosis of LGGs [43], no study has been focused on the correlation between collagen genes and tumor microenvironment of glioma. The tumor microenvironment consists of in ammatory cells, stromal cells, broblasts, vascular endothelial cells, and ECM [44].…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, elevated COL4A1 gene expression has been found to be associated with trastuzumab resistance in GC [27]. Several studied had reported that COL5A2 might function as crucial role in the initiation and progression of tumor by using bioinformatics technologies [28,29]. More importantly, COL5A2, was correlated with stromal scores in GC, promoted the recruitment of circulating monocytes into the TME and facilitated their differentiation into tumor-associated macrophages [30].…”
Section: Discussionmentioning
confidence: 99%